2011
DOI: 10.1128/aac.00199-11
|View full text |Cite
|
Sign up to set email alerts
|

Novel Trichomonacidal Spermicides

Abstract: Metronidazole, the U.S. Food and Drug Administration-approved drug against trichomoniasis, is nonspermicidal and thus cannot offer pregnancy protection when used vaginally. Furthermore, increasing resistance of Trichomonas vaginalis to 5-nitro-imidazoles is a cause for serious concern. On the other hand, the vaginal spermicide nonoxynol-9 (N-9) does not protect against sexually transmitted diseases and HIV in clinical situations but may in fact increase their incidence due to its nonspecific, surfactant action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 44 publications
(36 reference statements)
1
28
0
1
Order By: Relevance
“…Compound 12 exhibited promising RT inhibitory activity at 72.30%. Another nine compounds (13e16, 20e22, 25,26) showed moderate activity (38.40e59.62%). The standard nonnucleoside reverse transcriptase inhibitor (NNRTI), Nevirapine (NVP) showed 99.6% inhibition.…”
Section: Hiv-1 Rt (Reverse Transcriptase) Inhibitionmentioning
confidence: 97%
See 3 more Smart Citations
“…Compound 12 exhibited promising RT inhibitory activity at 72.30%. Another nine compounds (13e16, 20e22, 25,26) showed moderate activity (38.40e59.62%). The standard nonnucleoside reverse transcriptase inhibitor (NNRTI), Nevirapine (NVP) showed 99.6% inhibition.…”
Section: Hiv-1 Rt (Reverse Transcriptase) Inhibitionmentioning
confidence: 97%
“…Within hydroxyl compounds (17e21) the preferred groups in thiourea at N 4 of piperazine were phenethyl (21) and butyl (17) against MTZ susceptible and phenethyl (21) and cyclohexyl (19) against resistant strain. When trifluoromethylphenoxy (22e26) group was present at position-3 of propanamine chain then phenethyl group in thiourea at N 4 of piperazine (26) susceptible to resistant strains while these compounds lost activity by 2e4 times only. The results of antifungal activity of N-alkyl/aryl-4-(3-substituted-3-phenylpropyl)piperazine-1-carbothioamide (12e26, MIC 4.22e74.8 mM; Table 2) showed that the oxo derivatives (12e16) presented better activity profile than hydroxyl/4-trifluoromethylphenoxy derivatives (17e26).…”
Section: Structure Activity Relationship (Sar)mentioning
confidence: 99%
See 2 more Smart Citations
“…Piperazine (1) was protected selectively at one nitrogen (2) which on being reacted with carbon disulfide under alkaline conditions gave dithiocarbamate sodium salt (3). Compound (3) was reacted with alkyl halides to yield carbodithioic esters (4)(5)(6)(7)(8), which were deprotected with TFA to provide desired compounds (9)(10)(11)(12)(13), however, in the case of benzyl chloride an unusual N-benzyl product (14) was isolated in 20-30% yield (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%